Evaluation of obliteration of arteriovenous malformations after stereotactic radiosurgery with arterial spin labeling MR imaging. (2nd November 2017) - Kodera, Toshiaki; Arai, Yoshikazu; Arishima, Hidetaka; Higashino, Yoshifumi; Isozaki, Makoto; Tsunetoshi, Kenzo; Matsuda, Ken; Kitai, Ryuhei; Shimizu, Kazuhiro; Kosaka, Nobuyuki; Yamamoto, Tatsuya; Shioura, Hiroki; et al.
Abstract: Purpose: Complete obliteration of treated arteriovenous malformations (AVMs) can be diagnosed only by confirming the disappearance of arterio-venous (A-V) shunts with invasive catheter angiography. The authors evaluated whether non-invasive arterial spin labeling (ASL) magnetic resonance (MR) imaging can be used to diagnose the obliteration of AVMs facilitate the diagnosis of AVM obliteration after treatment with stereotactic radiosurgery (SRS). Material and methods: Seven patients with a cerebral AVM treated by SRS were followed up with ASL images taken with a 3T-MR unit, and received digital subtraction angiography (DSA) after the AVM had disappeared on ASL images. Three patients among the seven received DSA also after the postradiosurgical AVM had disappeared on conventional MR images but A-V shunt was residual on ASL images. Four patients among the seven received contrast-enhanced (CE) MR imaging around the same period as DSA. Results: ASL images could visualize postradiosurgical residual A-V shunts clearly. In all seven patients, DSA after the disappearance of A-V shunts on ASL images demonstrated no evidence of A-V shunts. In all three patients, DSA after the AVM had disappeared on conventional MR images but not on ASL images demonstrated residual A-V shunt. CE MR findings of AVMs treated by SRS did not correspond with DSA findings in three out of four patients. Conclusions: Findings of radiosurgically treated AVMs on ASL images corresponded with those on DSA. The results of this study suggest that ASL imaging can be utilized to follow up AVMs after SRS and to decide their obliteration facilitate to decide the precise timing of catheter angiography for the final diagnosis of AVM obliteration after SRS.